大阪大学2023前期理系数学解答 $\fbox{1}$
(1) $f(x)=\dfrac{1}{2}x^n$,$\displaystyle g(x)=(-1)^n\left\{\frac{1}{x+1}-1-\sum_{k=2}^n(-x)^{{k}-1}\right\}$,$h(x)=x^n-\dfrac{1}{2}x^{n+1}$ とおく.
ここで
\begin{align*}
g(x) & =(-1)^n\left\{\frac{1}{x+1}-1+x-x^2+x^3-\cdots -(-x)^{n-1}\right\} \\
& = (-1)^n\left\{\frac{1}{x+1}+(-1)\cdot\frac{1-(-x)^n}{1-(-x)}\right\} \\
& = (-1)^n\cdot\frac{1-1+(-x)^n}{x+1} \\
& = \frac{x^n}{x+1}.
\end{align*}
$0\le x \le 1$ なので
\begin{align*}
g(x)-f(x) & =\frac{x^n}{x+1}-\frac{1}{2}x^n=\frac{x^n(2-x-1)}{2(x+1)}=\frac{x^n(1-x)}{2(x+1)}\ge 0 \\
h(x)-g(x) & = x^n-\frac{1}{2}x^{n+1}-\frac{x^n}{x+1}=x^n\cdot\frac{2(x+1)-x(x+1)-2}{2(x+1)}=\frac{x(1-x)}{2(x+1)}\ge 0
\end{align*}
ゆえに $0\le x \le 1$ のとき $f(x)\le g(x) \le h(x)$ が成り立つ.
(2) (1) の結果より
\[ \int_0^1f(x)\,dx\le\int_0^1g(x)\,dx\le\int_0^1h(x)\,dx \]
が成り立つ.
\begin{align*}
\int_0^1f(x)\,dx & =\frac{1}{2}\left[\frac{x^{n+1}}{n+1}\right]_0^1=\frac{1}{2(n+1)} \\
\int_0^1h(x)\,dx & = \left[\frac{x^{n+1}}{n+1}-\frac{x^{n+2}}{2(n+2)}\right]_0^1=\frac{1}{n+1}-\frac{1}{2(n+2)}
\end{align*}
また
\begin{align*}
\int_0^1g(x)\,dx & =(-1)^n\bigg[\log(x+1)-x-\sum_{k=2}^n\frac{(-x)^k}{k}\cdot(-1)\bigg]_0^1 \\
& =(-1)^n\left\{\log 2-1+\sum_{k=2}^n\frac{(-1)^k}{k}\right\} \\
& =(-1)^n\left\{\log 2-1-\sum_{k=2}^n\frac{(-1)^{{k}-1}}{k}\right\} \\
& =(-1)^n\big(\log 2-a_n\big).
\end{align*}
よって
\[ \frac{1}{2(n+1)}\le (-1)^n\big(\log 2-a_n\big)\le \frac{1}{n+1}-\frac{1}{2(n+2)} \]
各辺に $-n(\le -2)$ をかけると
\[ -\frac{n}{2(n+1)}\ge (-1)^nn\big(a_n-\log 2\big)\ge -\left\{\frac{n}{n+1}-\frac{n}{2(n+2)}\right\} \]
ここで
\begin{align*}
\lim_{n\to\infty}\frac{n}{2(n+1)} & = \lim_{n\to\infty}\frac{1}{2(1+\frac{1}{n})}=\frac{1}{2} \\
\lim_{n\to\infty}\left\{\frac{n}{n+1}-\frac{n}{2(n+2)}\right\} & = \lim_{n\to\infty}\left\{\frac{1}{1+\frac{1}{n}}-\frac{1}{2(1+\frac{2}{n})}\right\}=1-\frac{1}{2}=\frac{1}{2}
\end{align*}
であるから $\displaystyle\lim_{n\to\infty}(-1)^nn\big(a_n-\log 2\big)=-\dfrac{1}{2}$.